Soil Organic Carbon Attenuates the Influence of Plants on Root-Associated Bacterial Community - Zhou, Yang; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2020)
Plant-derived carbon (PDC) released by roots has a strong effect on root-associated bacterial community, which is critical for plant fitness in natural environments. However, the freshly exuded PDC can be diluted by the ancient soil-derived carbon (SDC) at a short distance from root apices. Thus, the rhizosphere C pools are normally dominated by SDC rather than PDC. Yet, how PDC and SDC interact to regulate root-associated bacterial community is largely unknown. In this study, a grass species and a legume species were planted in two contrasting matrixes, quartz sand and soil, to assess the role of PDC and SDC in regulating root-associated bacterial community, and to explore whether SDC affects the influence of PDC on bacterial community in soil. Our results indicated that the legume plant showed significantly positive priming effect on soil organic matter decomposition but the grass plant did not. PDC significantly shaped bacterial community in sand culture as indicated by PCR-DGGE and high-throughput sequencing of bacterial 16S rRNA gene. Intriguingly, we found that dissimilarity of bacterial communities associated with two plant species and the percentage of specific OTUs in quartz sand were significantly higher than those in soil. Moreover, several biomarkers enriched by plants in quartz sand turned to be general taxa in soil, which indicated that SDC attenuated the regulation of bacterial community by PDC. Taken together, these results suggest that SDC interacted with PDC and the root-associated microbial community, thus acted as soil buffering component of biological process contributing to soil resilience. The importance of PDC in structuring rhizosphere bacterial community needs to be reconsidered in the context of wider contribution of other C pool, such as SDC.